Pharynx The Incredible Rendezvous Sites of Gas, Liquid and Solid - Wang, Tang-Chuan (IntechOpen, 2022)
The pharynx is an incredible structure in the human body. The pharynx moves food or water from the mouth to the esophagus and moves air from the nasal and oral cavities to the larynx or voice box. There are some conditions that can cause the pharynx to not function properly, affecting digestion, respiration, phonation, or sleep. One of the most challenging conditions is pharyngeal cancer. This book provides a comprehensive overview of the pharynx and addresses advances in the treatment of pharyngeal disorders, including surgery and reconstruction techniques.